“Only Daughter”: A Perennial Message for Empowerment of Females - Gouli, Mohan Raj (The Batuk, 2022)
Women perform their works from domestic to any outer world. In spite of being active within the territory of their household works, they have set several significant examples in political, economical, social, literary and other fields. In this context, Mary Wollstonecraft, Lydia E. Pinkham, Virginia Woolf, Margaret Thatcher, Indira Gandhi, Mother Teresa, Mahasweta Devi, Gayatri Chakravorty Spivak, Sandra Sisneros, Susri Parijat and Anuradha Koirala are a few examples of women activists who have contributed to the society and nations performing their best works in their respective fields. Their involvement, perhaps, was not as easy as we understand today; they must have undergone several complicated circumstances to work with patriarchal society. Such action and result oriented females' strategies and contributions/works can be fruitful for empowerment of women even today. This study tries to find out how Sandra Cisneros' work "Only Daughter" initiates for the empowerment of women these days, for it raises the issues of "subject matter as well as a desire for justice and a belief in the power of education to change our society for the better" (Tyson 116).